The Seroprevalence of Parvovirus B19 among Pregnant Women with Spontaneous Abortion in Thi-Qar province, Iraq - Khalid R. Majeed (Journal of Global Pharma Technology, 2018)
Background: Parvovirus B19 (B19 V) is a pathogenic for humans and the cause of erythema infectiosum, a common rash of childhood. B19 infection also causes severe disease such as chronic anemia in immunocompromised patients; aplastic crisis in the fetus can lead to cardiac failure, nonimmune hydrops, and fetal death in pregnant women.  Objective: To determine the seroprevalence of immunoglobulin (IgM, IgG) to Parvovirus B19 in pregnant women with spontaneous abortion.  Materials and Methods: Cross sectional study was carried out in 100 pregnant women who referred due to a spontaneous abortion that attended at Bunt AL- Huda hospital for maternity and children in Thi-Qar province, Iraq. Then, the blood samples were tested to assay of anti-human B19 specific IgM, and IgG using commercial enzyme-linked immunosorbent assays (DRG-Elisa kit, Germany). Furthermore, a questionnaire filled for all participants during samples collection. Results: Among study group the mean age was 27.35 years, with an age range 17-40 years. Seropositivity rate was 34% (34 cases) for an individual occurrence of human parvovirus B19 IgM alone and 38% (38 cases) for a similar individual rate of human parvovirus B19 IgG, Meanwhile,12 cases (12%) had both types of antibodies. There was no significant difference between the presence of antibody and age of pregnant women, gestational age, number of previous abortion, presence of children below the age of six. Conclusion: The results of this study showed (84%) of studied participants had a high susceptibility to parvovirus B19 in a way similar to that found in most countries. And also there might be a number of spontaneous abortions in which parvovirus infection caused fetal death. However, more studies are needed to prove the absolute role of parvovirus B19 in these abortions.Keywords: Pregnant women, Spontaneous abortion, Human parvovirus B19, ELISA.